2005
DOI: 10.1089/acm.2005.11.931
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Complementary and Alternative Medicine in Public Health Practice and Training

Abstract: This exploratory study provides insight into the potential role of CAM as an important resource in public health settings. Additional funding and research in this area is urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Despite this reasoning being highly plausible, our data do not allow to draw any conclusion about the impact of the observed incongruence between beginners' expectations and teachers' appraisals on the outcomes of the Taiji courses or the beginners' and/or teachers' course satisfaction. Still our findings may provide information of practical relevance: Since Taiji is not commonly practiced among health care professionals [53], our data collected from 136 Taiji teachers provides valuable insights into potential benefits of Taiji-beginners courses that might be helpful for health care professionals for their own as well as for their patients' information.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this reasoning being highly plausible, our data do not allow to draw any conclusion about the impact of the observed incongruence between beginners' expectations and teachers' appraisals on the outcomes of the Taiji courses or the beginners' and/or teachers' course satisfaction. Still our findings may provide information of practical relevance: Since Taiji is not commonly practiced among health care professionals [53], our data collected from 136 Taiji teachers provides valuable insights into potential benefits of Taiji-beginners courses that might be helpful for health care professionals for their own as well as for their patients' information.…”
Section: Discussionmentioning
confidence: 99%
“…Research is also needed to determine whether acknowledging and fostering the participation of massage therapists in the public health workforce increases positive health outcomes. (40) This research would be well-guided by Social Cognitive Theory, especially the construct of self-efficacy. If massage therapists have high selfefficacy (confidence in their ability to perform specific behaviors), this likely affects their behavior and hence their clients' health outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…furthermore, the research noted that these health professionals' personal use of CAM was also found significantly correlated with their professional use of CAM. 29 These studies demonstrate the need to include CAM in professional preparation courses, so that all health educators are adequately and equally prepared to discuss CAM with the nearly 40% of U.S. adults who use CAM with potential health risks and the more than 60% of U.S. adults who do not currently use CAM but might be missing out on potential health benefits of CAM therapies. 4 Training for health educators could help to dispel myths, correct terminology, report evidenced-based medical findings on CAM therapies, enhance knowledge, and explore CAM patient advocacy skills.…”
Section: Translation To Health Education Practicementioning
confidence: 91%
“…As of 2005, only a small number of accredited schools of public health even offer CAM courses in their curricula. 29 This presents a key challenge regarding discrepancies in public health trends (i.e., increased CAM use among both college populations and the general population) and public health education and training. To meet this need, CAM training should be incorporated into professional preparation programs for school health and community health educators.…”
Section: Translation To Health Education Practicementioning
confidence: 99%